A Rare Presentation of Hemothorax due to Left Hemithorax Penetrative Wound: An Operative Approach Requiring Segmentectomy - Adhia Endrika; Romy Deviandri; Ade Wirdayanto; Fakhrul Hendra; Briliant Briliant; Andrea Valentino (Journal of Medicine and Health, 2026)
Hemothorax is a medical emergency as blood accumulates inside the pleural space due to spontaneous, iatrogenic, or traumatic etiology. In general, hemothorax has a good prognosis. But severe hemothorax, especially those in vital areas, can lead to more invasive management. This case report aims to explore the presentation of massive hemothorax due to penetrative trauma and discuss suitable management approaches. A 16-year-old patient came due to spear wound through the left shoulder without exit wound. From primary assessment we found subcutaneous emphysema in the left lung, without compensation in airway and circulation system. A thoracocentesis intervention promptly performed as initial treatment. Secondary management proceeded with surgical thoracotomy which resulted in segmentectomy. Around 2-6% of patients of hemothorax patients need surgical intervention, and less than 2% will need segmentectomy intervention due to bleeding that cannot be corrected with surgical ligation. This case is one of the rare cases of hemothorax with segmentectomy. Although this patient did not have any respiratory nor circulatory complication, laceration in proximal hilum area leads to massive bleeding that damaged the lung parenchyma. Vigilant assessment in patients with penetrative trauma, especially in the left hemithorax, is essential to diagnose possible complication and execute evidence-based management plan.